Ultraestrutura e citoquímica do tubo digestivo de Hemisorubim platyrhynchos (Teleostei, Siluriformes, Pimelodidae) - Faccioli, Claudemir Kuhn [UNESP] (2015)
The knowledge of morphological characteristics of the digestive tract, associated with the processes of digestion and absorption, it is essential to understanding the physiology and nutrition of fish, assisting in planning diets to provide better management and success in farming. Thus, the aim of this study is to analyze the ultrastructural and cytochemical features of the digestive tract of adult specimen of Hemisorubim platyrhynchos to support cultivation in fish farms and preservation of the species. H. platyrhynchos is a carnivorous specie, distributed in the basins of the Orinoco, Amazonas, Paraguay, Uruguay and Paraná. This fish presents great potential for consumption, due to the animal size and meat quality. It is also used for ornamental fish due to the staining pattern of this species. However, this species is endangered in the São Paulo state, with reduced inventory and isolated populations. Thus, thirty specimens were killed and dissected to remove fragments of the esophagus, stomach (gastric ventricle) with cardiac, fundic and pyloric regions and intestine (anterior, middle, posterior and rectum). For ultrastructural studies, fragments were fixed in modified Karnovsky solution, post-fixed in osmium tetroxide and destinated for inclusion in the transmission electron microscopy routine. For cytochemical studies, tissue samples were fixed on appropriate solutions and destined for the following cytochemical techniques: impregnation with zinc iodide-osmium tetroxide - ZIO (targeting analysis of membranous organelles), method osmium-imidazole (to detect of lipid droplets), method for detection of alkaline and acid phosphatase and method for detection of acid glycoconjugates (ruthenium red). These techniques enabled a detailed analysis of the cellular characteristics of the epithelial lining, aiding in the understanding of cell physiology along the digestive tract of H. platyrhynchos